Risk prediction and outcomes in chronic kidney disease stage 3: a prospective cohort study in primary care - Shardlow, Adam (2019)
Introduction Chronic Kidney Disease (CKD) is common, and affects many people who are predominantly managed in primary care. Guidelines for management of CKD are often based around evidence from referred secondary care populations. Many risk factors for progressive CKD have been described, but not examined in a primary care population. Outcomes in CKD are variable, and concern long-term changes. Therefore, risk stratification is key to guide clinical management. This thesis will examine outcomes over 5 years in a cohort of people with CKD stage 3 recruited from primary care. It will evaluate cystatin C, Fibroblast Growth Hormone (FGF23), vitamin D and parathyroid hormone (PTH) as biochemical markers of risk in this population, and additionally will assess Skin autofluorescence (SAF) as a non-invasive measure of tissue advanced glycation endproducts (AGEs) and another potential strategy for risk stratification.